Momentum-resolved fingerprint of Mottness in layer-dimerized Nb3Br8 - Mihir Date; Francesco Petocchi; Yun Yen; Jonas A. Krieger; Banabir Pal; Vicky Hasse; Emily C. McFarlane; Chris Körner; Jiho Yoon; Matthew D. Watson; Vladimir N. Strocov; Yuanfeng Xu; et al. (Nature Communications)
Abstract Crystalline solids can become band insulators due to fully filled bands, or Mott insulators due to strong electronic correlations. While Mott insulators can theoretically occur in systems with an even number of electrons per unit cell, distinguishing them from band insulators experimentally has remained a longstanding challenge. In this work, we present a unique momentum-resolved signature of a dimerized Mott-insulating phase in the experimental spectral function of Nb3Br8: the top of the highest occupied band along the out-of-plane direction kz has a momentum-space separation Δk z = 2π/d, whereas that of a band insulator is less than π/d, where d is the average interlayer spacing. Identifying Nb3Br8 as a Mott insulator is crucial to understand its role in the field-free Josephson diode effect. Moreover, our method could be extended to other van der Waals systems where tuning interlayer coupling and Coulomb interactions can drive a band- to Mott-insulating transition.